The Role of the Myocardial Microvasculature in Mental Stress–Induced Myocardial Ischemia. Issue 4 (19th February 2016) - Ma, Huan; Guo, Lan; Huang, Daozheng; Wang, Lei; Guo, Liheng; Geng, Qingshan; Zhang, Minzhou
ABSTRACT: There is increasing evidence that mental stress can manifest as physical diseases. One such condition is mental stress–induced myocardial ischemia (MSIMI); a silent, transient, myocardial ischemic response to stressful conditions. We propose that the cardiac microvasculature may be an important site for the interplay between mental stress and MSIMI. This study is a review of the literature discussing the prevalence and emerging mechanisms underlying MSIMI. We identified several aspects underlying MSIMI, including psychological, genetic, and physiological causes. Several sources suggested that dysfunctional cardiac microvasculature might be a contributing factor in the development of stress‐induced myocardial ischemia. The literature also suggested that although MSIMI has distinct features and pathophysiology, its occurrence might indicate an increased future risk of cardiovascular events. We found that dysfunctional cardiac microvasculature may be the key point of interaction between mental stress and transient myocardial ischemia and that the development of MSIMI might be a "silent" indicator for future cardiac events.